2022
DOI: 10.1177/13591053221090850
|View full text |Cite
|
Sign up to set email alerts
|

Black (patients’) lives matter: Exploring the role of identity-safety cues in healthcare settings among Black Americans

Abstract: Two online experiments investigated whether hypothetical physicians’ use of an identity-safety cue acknowledging systemic injustice (a Black Lives Matter pin) improves Black Americans’ evaluations of the physician and feelings of identity-safety. Across studies, findings showed that when a White physician employed the identity-safety cue, Black Americans reported stronger perceptions of physician allyship and increased identity-safety (e.g. trust). As predicted, use of the identity-safety cue produced smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For example, dominant-group members who express more positive intergroup attitudes experience less anxiety and more comfort interacting with other individuals from different social groups (e.g., cross-race and cross-social-class interactions; Brannon et al, 2017; Townsend et al, 2021). Research has shown that dominant-group members’ actual intergroup attitudes (e.g., Plaut et al, 2009) and inferred beliefs (e.g., signaled through behaviors such as wearing a BLM pin; Derricks et al, 2022) are linked to engagement and trust of marginalized-group members within mainstream institutions (e.g., workplaces, medical settings).…”
Section: Intergroup Attitudes: Out-group Exposure To Pride-and-prejud...mentioning
confidence: 99%
“…For example, dominant-group members who express more positive intergroup attitudes experience less anxiety and more comfort interacting with other individuals from different social groups (e.g., cross-race and cross-social-class interactions; Brannon et al, 2017; Townsend et al, 2021). Research has shown that dominant-group members’ actual intergroup attitudes (e.g., Plaut et al, 2009) and inferred beliefs (e.g., signaled through behaviors such as wearing a BLM pin; Derricks et al, 2022) are linked to engagement and trust of marginalized-group members within mainstream institutions (e.g., workplaces, medical settings).…”
Section: Intergroup Attitudes: Out-group Exposure To Pride-and-prejud...mentioning
confidence: 99%
“…Minoritized groups often face concerns about negative treatment and belonging in work contexts (Shapiro & Neuberg et al, 2007;Sinclair & Kunda et al, 1999;Steele et al, 2002) and look to environmental cues to determine whether they will be valued and how to present themselves in that environment. For example, recruitment brochures that celebrate diversity (Gündemir et al, 2016;Purdie-Vaughns et al, 2008; also see , spaces dedicated to marginalized groups (Chaney & Sanchez et al, 2018;Kirby, Rego et al, 2020), identity-relevant academic curricula (Brannon et al, 2015) and the presence of allies or similar others (Derricks et al, 2023;Hildebrand et al, 2020;Johnson & Pietri et al, 2020;Murphy et al, 2007;Pietri et al, 2019) can all signal belonging and identity safety to stigmatized groups. Evidence for these processes has so far stemmed mainly from research with women and minoritized racial groups, largely in the United States.…”
Section: Identity Safety Cues For the Sexual Minoritiesmentioning
confidence: 99%
“…Minoritized groups often face concerns about negative treatment and belonging in work contexts (Shapiro & Neuberg et al., 2007; Sinclair & Kunda et al., 1999; Steele et al., 2002) and look to environmental cues to determine whether they will be valued and how to present themselves in that environment. For example, recruitment brochures that celebrate diversity (Gündemir et al., 2016; Purdie‐Vaughns et al., 2008; also see Kirby & Kaiser et al., 2020; Kirby et al., 2020), spaces dedicated to marginalized groups (Chaney & Sanchez et al., 2018; Kirby, Rego et al., 2020), identity‐relevant academic curricula (Brannon et al., 2015) and the presence of allies or similar others (Derricks et al., 2023; Hildebrand et al., 2020; Johnson & Pietri et al., 2020; Murphy et al., 2007; Pietri et al., 2019) can all signal belonging and identity safety to stigmatized groups. Evidence for these processes has so far stemmed mainly from research with women and minoritized racial groups, largely in the United States.…”
Section: Introductionmentioning
confidence: 99%